2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5626194
|View full text |Cite
|
Sign up to set email alerts
|

Contact stresses in a patient-specific unicompartmental knee replacement

Abstract: A custom, patient-specific unicompartmental knee replacement was developed using a unsupervised neural network trained on a database of healthy knee geometries. This custom implant was then compared to a conventional implant in terms of contact stress in a Finite Element Model. The custom implant experienced lower contact stresses at the tibiofemoral joint compared to the conventional implant. The custom implant stresses were further reduced with the use of a customized mobile bearing. The custom implant also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…Under axial force, the peak contact pressure values of mobile‐bearing UKA were ∼45% of gait cycle. Heever et al reported a peak contact pressure of 11.1 MPa, which is similar to our value of 14.2 MPa for mobile‐bearing UKA. The contact pressure on the superior surface of the mobile‐bearing PE insert was only two‐thirds that on the fixed‐bearing PE insert during the gait cycle.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Under axial force, the peak contact pressure values of mobile‐bearing UKA were ∼45% of gait cycle. Heever et al reported a peak contact pressure of 11.1 MPa, which is similar to our value of 14.2 MPa for mobile‐bearing UKA. The contact pressure on the superior surface of the mobile‐bearing PE insert was only two‐thirds that on the fixed‐bearing PE insert during the gait cycle.…”
Section: Resultssupporting
confidence: 90%
“…The contact area in mobile‐bearing UKA at maximum contact pressure was ∼4.2 times greater than that of the fixed‐bearing UKA. Contact pressure was consistent with corresponding values of a previously published FE study . Under axial force, peak contact pressure values of fixed‐bearing UKA were found at ∼43% of the gait cycle.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The CAD software generated three customized J-curves for the trochlear grooves and the medial and lateral condyles from the normal articular geometry of the subject in this study (26)(27)(28). The 3D reconstructed customized geometry of the bony structure and surface data were used to develop the geometry of customized TKA.…”
Section: Design Of Ps Tkamentioning
confidence: 99%
“…The sagittal geometry of the patient's bone was completely used for the geometry of the customized femoral component. The CAD software generated three customized J-curves for the trochlear grooves and the medial and lateral condyles from the normal articular geometry of the subject in this study (26)(27)(28). Planes were introduced into the condyles in sagittal view in which the curves were used to extract the articulating surface geometry ( Figure 1).…”
Section: Design Of Ps Tkamentioning
confidence: 99%